2015
DOI: 10.1155/2015/415961
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Properties of Activated Carbon Prepared from Tamarind Seeds by KOH Activation for Fe(III) Adsorption from Aqueous Solution

Abstract: This research studies the characterization of activated carbon from tamarind seed with KOH activation. The effects of 0.5 : 1–1.5 : 1 KOH : tamarind seed charcoal ratios and 500–700°C activation temperatures were studied. FTIR, SEM-EDS, XRD, and BET were used to characterize tamarind seed and the activated carbon prepared from them. Proximate analysis, percent yield, iodine number, methylene blue number, and preliminary test of Fe(III) adsorption were also studied. Fe(III) adsorption was carried out by 30 mL c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(131 citation statements)
references
References 35 publications
9
100
1
4
Order By: Relevance
“…The spectra of prepared 10%, 15%, 20% and 25% AC/K showed a decreasing trend in the broad peak of C-O around 900-1300 cm -1 and the C=C absorption band around 1500 -1650 cm -1 . This result in agreement by the previous studies [11,17] indicating that by increasing the amount of activating agent, the activation reaction would increase and more weak bonds disappeared by thermal degradation.…”
Section: Fourier Transfer Infrared Spectroscopy Analysissupporting
confidence: 93%
“…The spectra of prepared 10%, 15%, 20% and 25% AC/K showed a decreasing trend in the broad peak of C-O around 900-1300 cm -1 and the C=C absorption band around 1500 -1650 cm -1 . This result in agreement by the previous studies [11,17] indicating that by increasing the amount of activating agent, the activation reaction would increase and more weak bonds disappeared by thermal degradation.…”
Section: Fourier Transfer Infrared Spectroscopy Analysissupporting
confidence: 93%
“…The study was conducted according to American Society of Testing and Materials (ASTM, 2006). The fixed carbon content obtained from this study is higher than other biomass precursor reported before such as rice husk biocarbon (17.34%) (Kizito et al, 2015), tamarind seed biocarbon (28.89%) (Mopoung et al, 2015), and Leucaena leucocephala bark (18.10%) (Anupam et al, 2011). This may be due to the structural compositional difference in terms of cellulose, hemicellulose and lignin that build up the cell wall of the precursor used (Hodgson et al, 2016).…”
Section: Adsorption Of Methylene Bluecontrasting
confidence: 56%
“…Iodine number is also depicted as an indication of total surface area. The typical range for iodine number required for waste water application is 500-1200 mg/g (Mopoung et al, 2015). The results of iodine number determination is shown in Table 2.…”
Section: Adsorption Of Methylene Bluementioning
confidence: 99%
“…This might be because of the activation process, the use of phosphoric acid as activating agent, which helped the pores development thus indirectly increased the surface area obtained [16]. This is supported by the Nitrogen Gas Adsorption Single Point Analysis results where the surface area of the TSC obtained was higher compared to the tamarind seed activated carbon prepared with base activating agent (KOH) [17]. …”
Section: Introductionmentioning
confidence: 87%